COMPARISONS OF LINEAR REGRESSION MODELS FOR PROPERTIES OF ALKALIACTIVATED BINDER CONCRETE - Kar, Arkamitra; Halabe, Udaya B.; Ray, Indrajit; Unnikrishnan, Avinash (European Scientific Journal, ESJ, 2015)
Concrete with alkali-activated binder (AAB) is increasingly considered as a better alternative to conventional portland cement (PC) concrete due to its superior sustainable and green properties. In order to promote the practical usage of AAB concrete, a previous study by the present authors proposed models on correlations among their mechanical and nondestructive properties. The present study extends the previous knowledge by proposing new improved models using linear regressions to predict compressive strengths and modulus of elasticity from ultrasonic pulse velocities. The models are developed for both unstressed and stressed AAB concrete with different curing temperatures. The accuracies of the models are compared with both sum of squares due to errors (SSE) and R2 depending on the type of equations; and the new models are found to be more accurate compared to the previous models.